Proteases Revisited: Roles and Therapeutic Implications in Fibrosis - Jakub Kryczka; Joanna Boncela (Mediators of Inflammation)
Proteases target many substrates, triggering changes in distinct biological processes correlated with cell migration, EMT/EndMT and fibrosis. Extracellular protease activity, demonstrated by secreted and membrane-bound protease forms, leads to ECM degradation, activation of other proteases (i.e., proteolysis of nonactive zymogens), decomposition of cell-cell junctions, release of sequestered growth factors (TGF-β and VEGF), activation of signal proteins and receptors, degradation of inflammatory inhibitors or inflammation-related proteins, and changes in cell mechanosensing and motility. Intracellular proteases, mainly caspases and cathepsins, modulate lysosome activity and signal transduction pathways. Herein, we discuss the current knowledge on the multidimensional impact of proteases on the development of fibrosis.